х=9(х-2,1)
И
2(7х-7)=7(х-3)+7​

lol1027 lol1027    3   26.04.2020 16:06    0

Ответы
alexeyvinogradp0do9x alexeyvinogradp0do9x  13.10.2020 21:53

1) 3.6  2) 0

Пошаговое объяснение:

1) 2,7+3х=9(х-2,1)

  2.7+3x=9x-18.9

  3x-9x=-18.9-2.7

      -6x=-21.6 | :(-6)

          x=3.6

2) 2(7х-7)=7(х-3)+7

   14x-14=7x-21+7

    14x-7x=-21+7+14

           7x=0 | :7

             x=0

             

ПОКАЗАТЬ ОТВЕТЫ
Виталина5413 Виталина5413  13.10.2020 21:53

2,7 + 3х = 9 ( х - 2,1)

2,7 + 3х = 9х - 18,9

3х - 9х = - 18,9 - 2,7

-6х = - 21,6

х = - 21,6 : (-6)

х = 3,6

2( 7х-7)=7(х-3)+7

14х-14=7х-21+7

14х-7х=-21+7+14

7х=0

х=0:7

х= 0

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика